Analysis Of The Potential And Economic Feasibility Of Seaweed Cultivation In Sajoanging District, Wajo Regency - Syamsuri Syamsuri; Hasria Alang (UNIVED Press, Dehasen University Bengkulu, 2022)
One of the factors that can improve the community's economy is utilization in the fisheries and marine sector. Indonesia, which is a maritime country, certainly has the opportunity to maximize the marine sector, one of which is by cultivating seaweed. Seaweed or algae is a type of commodity that has a very high economic value because it is useful in industries such as pharmaceuticals, cosmetics and foodstuffs. One of the areas in South Sulawesi that does seaweed cultivation is Sajoanging District. The purpose of this study is to analyze the potential and economic feasibility of seaweed cultivation in Sajoanging District, Wajo Regency. The method is carried out using purpose sampling, sampling is by means of Simple Random Sampling, data collection is carried out by means of observation, documentation and interviews. The results showed that the income of the people who cultivate seaweed was 97,438,400.00 every year, while the R/C ratio was 2.6. This shows that seaweed cultivation has economic potential because it can improve the community's economy. This cultivation is also very feasible to continue because the value of R/C> 1 is 2.6.